ANALISIS PERILAKU PENGGUNAAN LPG PADA RUMAH TANGGA DI KOTA BOGOR - Pranadji, Diah Krisnatuti; Djamaludin, Moh. Djemdjem; Kiftiah, Nuriza (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2010)
The aim of this research is to analyze behaviour using of the household fuel in Bogor. This research design to use cross sectional and survey methods through the process of random sampling procedure. The total of samples is 80 families. This research use descriptive analysis that contains of secondary data, literature study, and primary data. To analyze the data is used Spearman correlation and linear Regression. About 80% of respondents use only LPG as domestic fuel, 17,5% use LPG fuel and other fuels, and 2,5% use other of LPG. This result showed that 72,5% have a fairly good perception of LPG fuel, 77,5% of housewives have a good knowledge level, and 81,2% housewives have good attitude towards LPG. In general, one tube of LPG (3kg) has wasted for 7-14 days and cost average of fuel is about Rp 54.781,00/month. Housewife age and family income per capita influence use frequency of LPG. Trade that use LPG, total of family member, and housewives knowledge are influence total using of LPG tube (3kg)/month and expenditure for LPG/month.